Prediction of Full Field Dynamic Strain from Limited Sets of Measured Data - Peter Avitabile; Pawan Pingle (Shock and Vibration)
Dynamic response is an important consideration for design of structures due to operating or occasional loadings. The resulting dynamic stress strain is also of concern for fatigue and structural health monitoring. Typically, the actual loading and structural condition (boundary conditions, environmental condition, geometry, mechanical properties, etc.) are not necessarily known. Much effort is expended in attempting to identify the loads and appropriate model for prediction of these types of events. At best, the forces and actual boundary conditions are approximate and have an effect on the overall predicted response and resulting stress-strain that is identified for subsequent evaluation.